Emergence of antimicrobial resistance among invasive Haemophilus influenzae isolates in Belgium: epidemiology and genomic characterization - Ms Magali Wautier; Dr Ricardo El Nouwar; Mr Benoit Prevost; Ms Farida Ahajjam; Ms Ariane Deplano; Ms Rim Fekkak; Dr Nicolas Yin; Dr Maya Hites; Prof Delphine Martiny (International Journal of Infectious Diseases)
Introduction: Haemophilus influenzae (Hi) is a significant cause of invasive infections, including meningitis and sepsis. The emergence of resistant strains has prompted the World Health Organization to include Hi on its priority list for research and development of new antibiotics. The objective of this study was to describe the epidemiology of invasive Hi strains in Belgium, with a particular focus on beta-lactam resistance. Methods: A retrospective analysis of invasive Hi strains referred to the NRC from 2018 to 2023 was conducted. All national laboratories are required to submit invasive Hi strains to the NRC. There, the strains are identified using MALDI-TOF MS and antimicrobial susceptibility testing is performed following EUCAST guidelines. For isolates showing reduced susceptibility to beta-lactams, the ftsI gene is sequenced. Selected isolates (e.g. in the case of suspicion of a cluster) undergo whole-genome sequencing. Results: A total of 804 strains were included, with the lowest incidence rate per 100.000 population observed in 2020 and 2021 (0.75/100.000 inhabitants). The male-to-female ratio was 1.13, with a male predominance observed in individuals under the age of 5. Over 75% of strains were non-typeable Hi (NTHi). The resistance rates for ampicillin and amoxicillin-clavulanic acid were 18.7% and 4.6%, respectively. Mutations in the ftsl gene associated with decreased susceptibility to beta-lactams varied from 11.5% to 17.7%. In 2023, mutations associated with high levels of beta-lactam resistance (group III/III-like) were detected in six NTHi strains (3.3%), five of which exhibited identical ftsI mutations (D350N, S357N, M377I, S385T, R517H, T532S). Four of the five isolates belonged to the MLST clonal complex 3 and exhibited a similar phenotypic profile namely biotype II, absence of beta-lactamase, resistance to cefuroxime and trimethoprim-sulfamethoxazole. Three of the four isolates were recovered at the beginning of the year from patients with pneumonia residing in Limburg. A whole genome single nucleotide polymorphism (SNP) analysis demonstrated they had less than four SNPs of difference. Discussion: This study provides a comprehensive overview of the epidemiology of invasive Hi infections in Belgium. As with other respiratory pathogens, the COVID-19 pandemic has had a significant impact on the epidemiology of invasive Hi infections. The distribution of sex and age was consistent with global trends, as was the prevalence of NTHi. The prevalence of beta-lactam resistance was comparable to that observed in other European countries. It is noteworthy that, for the first time in Belgium, six strains of Hi have emerged, displaying mutations associated with high-level beta-lactam resistance. Furthermore, WGS analysis has confirmed the existence of a cluster of three of these strains. Conclusion: Vigilant surveillance of circulating Hi strains and research are fundamental to addressing evolving challenges and guiding future interventions, including the adaptation of treatment guidelines.